What kind of calcite? Disclosing the origin of sparry calcite temper in ancient ceramics. (May 2021) - Maritan, Lara; Ganzarolli, Giovanna; Antonelli, Fabrizio; Rigo, Manuel; Kapatza, Angeliki; Bajnok, Katalin; Coletti, Chiara; Mazzoli, Claudio; Lazzarini, Lorenzo; Vedovetto, Paolo; Chavarría Arnau, Alexandra
Abstract: The addition of temper in the pottery manufacturing process is attested since Prehistoric Times and is still a production choice adopted in the ceramic industry. When the temper is composed of minerals and rocks which outcrop in regions distant from each other, new questions about the production technology arise. Such situations can be explained by considering the recycling of imported rocks, including those used for architectonic elements or sculptures, mainly coming from contemporary or earlier buildings, a practice that was widely diffused during the Roman and successive periods. This study presents evidence of the deliberate addition of recycled white marbles and sparry calcite (probably from calcareous sinters/calcite alabasters) within the long-lived production (between the 4th and 14th century CE) of coarse and cooking ware in north-eastern Italy. The petrographic analysis of about 200 potsherds attested the use of marble as unusual kind of temper, in addition to fragments of sparry calcite, in about half of the repertoire. The occurrence of different types of marbles, associated with rocks and minerals typical of the alluvial deposits of the eastern Po plain as well as locally available rocks (Euganean Hills trachyte), clearly pointed to the intentional addition of recycled marble fragments from ancient spolia, excluding the hypothesis that the pottery was imported from other regions. Detailed petrographic and microstructural analysis, including maximum grain size (MGS), accessory minerals (when observed) and grain boundary shapes allowed us to limit the provenance of these marbles to the most important Mediterranean classical source regions. These conclusions have been confirmed by the oxygen and carbon stable isotope data derived from marbles and calcite fragments mechanically separated from the ceramic paste. Some fragments of sparry calcite were characterised by very negative δ 13 C values, significantly different from known marble varieties, and typical of calcite crystallised in superficial geological environments, consistent with calcareous sinters, such as calcite alabasters. Moreover, a series of firing experiments were carried out in the temperature interval between 450 °C and 800 °C, both reproducing oxidising and reducing conditions, on clay pastes tempered with Carrara marble, and fired, to evaluate whether these anomalous δ 13 C values observed in the ancient ceramic inclusions could also be related to the firing process. Highlights: Use of exogenous temper in local pottery production during Late Roman and Medieval times. O and C stable isotope analysis disclosed the geological origin of sparry calcite and marble temper. Firing experiments allowed definition of the influence of temperature on calcite O and C stable isotopes. archaeometric analysis revealed the reuse of white marbles and calcite alabasters.